Design of Tourism Arabic Teaching Materials for Tourism Awareness Groups: The Case of Cisaat Tourism Village in Subang, West Java - Ihwan Rahman Bahtiar*; Mohamad Sarip; Chakam Failasuf; Siti Jubaidah (Riwayat: Educational Journal of History and Humanities, 2023)
Cisaat Village in Subang District is a developing tourist village increasingly visited by Middle Eastern tourists. Unfortunately, the Tourism Awareness Group (pokdarwis) in Cisaat has not yet mastered Arabic communication skills, although they have already gained experience in learning Arabic. This research aims to develop Arabic teaching materials for tourism village groups in Indonesia. This study uses the research and development method of Thiagarajan's 4D model. The instruments of this study were questionnaires distributed to 30 members of Pokdarwis and unstructured interviews. The data analysis used was quantitative descriptive. The results showed a need to prepare Arabic teaching materials for Tourism Awareness Groups (Pokdarwis) at Cisaat Tourism Village. Educational materials are designed in e-audio books, and the learning topics presented are transportation, homestay (hotel), and transactions.